What is next for the neurobiology of temperament, personality and psychopathology?. (June 2022) - Trofimova, Irina; Bajaj, Sahil; Bashkatov, Sergey A; Blair, James; Brandt, Anika; Chan, Raymond C K; Clemens, Benjamin; Corr, Philip J; Cyniak-Cieciura, Maria; Demidova, Liubov; Filippi, Courtney A; Garipova, Margarita; et al.
Highlights: Paper summarizes the multidisciplinary discussion by authors of this Theme Issue Ten directions were identified in international and multidisciplinary cooperation. There is a need in principles underlying biobehavioural taxonomies, not just stats Many continua to be accommodated: clinic-health, ontogenetic, sex, context etc Non-brain biomarkers, language biases, conceptual mix-ups, new math to be improved. Abstract : This paper represents the outcome of a multidisciplinary discussion on what works, what does not, and what can be improved, in ongoing work on biobehavioral taxonomies and their biomarkers. The authors of this paper, representing a wide spectrum of biobehavioral disciplines (clinical, developmental, differential psychology, neurophysiology, endocrinology, psychiatry, neurochemistry, and neurosciences), have contributed more extensive opinions to the Theme Issue 'Neurobiology of temperament, personality and psychopathology: what's next?'. The authors identified 10 directions in international and multidisciplinary cooperation, and multiple insights for 'what is next' for each of these directions.